2019
DOI: 10.1177/2045894018796804
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary remodeling in fattened beef cattle: a naturally occurring large animal model of obesity‐associated pulmonary hypertension with left heart disease

Abstract: The obesity epidemic in developed societies has led to increased cardiovascular diseases including pulmonary hypertension associated with left heart disease (PH-LHD), the largest and fastest-growing class of PH. Similar to obese humans, PH and heart failure (HF) are increasingly recognized in North American fattened beef cattle. We hypothesized that PH and HF in fattened beef cattle are novel, phenotypically distinct manifestations of bovine PH arising from left ventricular (LV) dysfunction similar to obesity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 49 publications
(86 reference statements)
3
32
0
Order By: Relevance
“…In that same study, localized hypoxia resulting from respiratory disease was a risk factor, given that cattle treated for respiratory disease were 2-3 times more likely to die of RHF than cattle not treated for respiratory disease. 21 Although high altitude is a well-established factor, previous studies 15,20,21 indicate that obesity and potentially coronary artery disease and left-heart dysfunction are likely major contributing factors to pulmonary hypertension and right-sided heart failure, and may have played a role in disease in the cattle in our study. Cattle are now fed to heavier finishing weights, with abdominal fat accumulation causing hypoxia through hypoventilation.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In that same study, localized hypoxia resulting from respiratory disease was a risk factor, given that cattle treated for respiratory disease were 2-3 times more likely to die of RHF than cattle not treated for respiratory disease. 21 Although high altitude is a well-established factor, previous studies 15,20,21 indicate that obesity and potentially coronary artery disease and left-heart dysfunction are likely major contributing factors to pulmonary hypertension and right-sided heart failure, and may have played a role in disease in the cattle in our study. Cattle are now fed to heavier finishing weights, with abdominal fat accumulation causing hypoxia through hypoventilation.…”
Section: Discussionmentioning
confidence: 64%
“…These changes likely preceded "muscularization, medial hypertrophy, adventitial fibrosis, and vasa vasorum hyperplasia of the pulmonary" arteries and, in turn, was "associated with the sequela of right ventricular remodeling." 15 Although coronary artery remodeling is thought to play a role in the pathogenesis of obesity-related congestive heart failure in feedyard cattle, 15 interestingly, intramural coronary arteriosclerosis is now recognized to commonly occur subclinically in slaughtered veal calves and beef cattle. 4 Notably, 1 of 3 controls in our study had coronary arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1970’s, bovine congestive heart failure (BCHF) has become increasingly common in feedlot cattle maintained at the low to moderate altitudes of the North American Plains (800 to 1,600 m) 5 . However, it is uncertain whether hypobaric hypoxia is the underlying cause of BCHF in these cattle, and evidence suggests that left heart dysfunction may initiate BCHF 6 . Histopathological assessment of cardiopulmonary tissues obtained from affected cattle fattened at 544-1,420 m revealed significant ventricular fibrosis, abundant cardiac adipose depots, coronary artery injury, and pulmonary venous remodeling 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is speculated that the conditions reflect distinct etiologies owing to the differing management practices that exist between ranches and feedlots. Krafsur et al, (2019) found that the physiology of FHD is characterized as significant pathophysiologic remodeling of the left ventricle and pulmonary venous circulation accompanying right heart and pulmonary arterial remodeling. Conversely, HMD has been characterized as pulmonary hypertension and right ventricular dysfunction ( Rhodes, 2005 ).…”
Section: Introductionmentioning
confidence: 99%